Fourth-grade emergent bilinguals' uses of functional grammar analysis to talk about text. (December 2017) - Symons, Carrie; Palincsar, Annemarie Sullivan; Schleppegrell, Mary J.
Abstract: While decades of research on reading comprehension strategy instruction has yielded significant insights into the effective use of comprehension strategies, less is known about how students—in particular students who are learning English as an additional language—can leverage their knowledge of language to make meaning with text. This descriptive case study provides insight into the ways talk about language, using a functional grammar, supports a group of fourth-grade emergent bilinguals. Students construct coherent mental representations of text by attending to linguistic features that they had learned to identify during the preceding school year, using a semantically-based linguistic metalanguage from systemic functional linguistics. Their connection of language forms and meanings in think-alouds and interviews suggests that functional grammar analysis holds promise as an instructional tool with which teachers can guide students' attention to the central meanings in text. Highlights: Informational science texts present linguistic challenges for emergent bilinguals. SFL offers a metalanguage with which emergent bilinguals can talk about text. Readers' attention to language features relates to the meanings they construct. Functional grammar analysis may support emergent bilinguals' meaning-making.